Rezension von: Alber, Wolfgang; Frahm, Eckart, Waßner, Manfred, Baden-Württemberg - Kohl, Herbert (Württembergisch Franken, 2000)
Wolfgang Alber, Eckart Frahm, Manfred Waßner, Baden-Württemberg. Kultur und Geschichte in Bildern, Stuttgart (Theiss) 1999. 160 S„ 230 meist färb. Abb.